MINIMUM INHIBITORY CONCENTRATION OF CEFTAZIDIME AVIBACTAM IN EXTENDED SPECTRUM BETA LACTAMASE PRODUCING PSEUDOMONAS AERUGINOSA (The Research of Medical Science Review, 2025)
Background: Antibiotic resistance has emerged as a great challenge for clinicians and researchers across the globe. Pseudomonas aeruginosa can quickly develop resistance to commonly used antimicrobial agents. In this situation, combination antibiotic plays significant role in treatment. Ceftazidime/avibactam, an emerging combination drug is particularly useful for treating gram negative infections. Methodology: This cross-sectional study was conducted from November 2024 to April 2025. This study enrolled seventy patients having infection and both males and females of all age groups. The different clinical samples were collected from patients. Pseudomonas aeruginosa was obtained from the clinical specimens from patients presented to the tertiary care hospital. The ceftazidime-resistant strains were screened for extended spectrum beta lactamase using the Calibrated Dichotomous Sensitivity Test. The activity of ceftazidime/avibactam was assessed using the disc diffusion (30/20 µg) method. For the detection of minimum inhibitory concentration, ceftazidime/avibactam E strips (Liofilchem MTS) was used. The collected data was entered in a excel sheet and analyzed by the Statistical Package for the Social Sciences version 27.0 software. Results: From all (n=70) patients, 42 (60.0%) were males and 28 (40.0%) were females. Most Pseudomonas aeruginosa were isolated from the medicine ward (n=31, 44.28%), and from urine samples (n=40, 57.14%). Among all Pseudomonas aeruginosa, 44 (62.85%) showed positive results for ESBL production while 26 (37.15%) showed no production of ESBL enzyme. Among all ESBL producing Pseudomonas aeruginosa, 41 (93.18%) isolates were sensitive, while, 03 (6.81%) were resistant to ceftazidime/avibactam. According to MIC, 41 (93.18%) extended spectrum beta lactamase producing Pseudomonas aeruginosa were sensitive, while, 03 (6.81%) were resistant to ceftazidime/avibactam. Conclusion: The observed minimum inhibitory concentration demonstrate that ceftazidime/avibactam retains significant in vitro activity against extended spectrum beta lactamase producing Pseudomonas aeruginosa, suggesting as a valuable therapeutic option.